Biochar one-off application for paddy soil 15N loss improvement: evidence from a two-year experiment - Gao, Jiping; Sui, Yanghui; Zhang, Zhongcheng; Zhang, Kai; Jiang, Hongfang; Liu, Yuzhuo; Sun, Zhongcheng; Bing, Xinyue; Zhao, Yanze; Zhang, Wenzhong (Frontiers in Plant Science, 2025)
The aim of this study was to quantify the impact of biochar one-off application on split application of nitrogen fertilizers. We used the 15N tracer technique to explore the effects of biochar on greenhouse gas (GHG) emissions and NUE during three growth stages (tillering, panicle initiation, and ripening). Total nine treatments incorporated three biochar levels (0, C0; 15, C1; 45 t ha−1, C2) with three N levels (0, N0; 168, N1; conventional N fertilization at 210 kg N ha−1, N2). The high N2O emission rate during the tillering stage was significantly affected by biochar application and its interaction with N fertilization in both years, with 2016 yielding higher emissions (15.8%–65.2% of the total). Optimizing biochar application with a focus on the tillering and panicle initiation stages can helped mitigate global warming potential (GWP) in the initial application. Rice yields were highest in N2C0 and N2C2 treatments across years, which were 13.0% and 8.5% higher than yield in N1C0, respectively. The base fertilizers in 2 years reduced the 15N loss rate (NLR) in N1C2 treatment by 49.5% and 38.6% compared with N1C0, respectively. In the first year, the N recovery efficiency (NRE) in N1C2 treatment decreased by 55.2%, 44.0%, and 21.4% for base, tiller, and panicle fertilizers, respectively, compared to and N2C1 decreased the NRE of the base fertilizers by 27.9% in the following year. No significant differences in the NRE of tiller and panicle fertilizers were observed between N1C1 and N2C1 treatments in the following year. This study underscores the potential of biochar as a an environmentally friendly soil amendment for N loss reduction in rice systems. Biochar one-off application plays a role in mitigating GHG emissions, particularly during different fertilization periods which contributes to more sustainable agricultural practices.